Animal Coloration in the Anthropocene - Koneru, Manisha; Caro, Tim (Frontiers in Ecology and Evolution, 2022)
Natural habitats are increasingly affected by anthropogenically driven environmental changes resulting from habitat destruction, chemical and light pollution, and climate change. Organisms inhabiting such habitats are faced with novel disturbances that can alter their modes of signaling. Coloration is one such sensory modality whose production, perception and function is being affected by human-induced disturbances. Animals that acquire pigment derivatives through diet are adversely impacted by the introduction of chemical pollutants into their environments as well as by general loss of natural habitat due to urbanization or logging leading to declines in pigment sources. Those species that do manage to produce color-based signals and displays may face disruptions to their signaling medium in the form of light pollution and turbidity. Furthermore, forest fragmentation and the resulting breaks in canopy cover can expose animals to predation due to the influx of light into previously dark environments. Global climate warming has been decreasing snow cover in arctic regions, causing birds and mammals that undergo seasonal molts to appear conspicuous against a snowless background. Ectotherms that rely on color for thermoregulation are under pressure to change their appearances. Rapid changes in habitat type through severe fire events or coral bleaching also challenge animals to match their backgrounds. Through this review, we aim to describe the wide-ranging impacts of anthropogenic environmental changes on visual ecology and suggest directions for the use of coloration both as an indicator of ecological change and as a tool for conservation.